PERANCANGAN APLIKASI PERPUSTAKAAN BERBASIS MOBILE DENGAN LAYANAN FAQ MENGGUNAKAN CHATBOT - Pramudya, Fillah Aby; Aji, Adam Sekti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study explores the development of a mobile-based library application equipped with an FAQ chatbot to enhance the efficiency of library management at SMA Negeri 2 Tumijajar. The application is designed to facilitate user access to library services such as book searches, borrowing, and returning, while also providing automated responses to frequently asked questions. The research employs the Research and Development (R&D) method, encompassing several stages: needs analysis, design, development, testing, and evaluation. Testing results indicate that the application features an intuitive interface, functions effectively across various devices, and is regarded as user-friendly by both library staff and students. Furthermore, the chatbot service has proven to be effective in addressing common inquiries, thereby reducing the workload of library staff. The study concludes that the mobile-based library application with an FAQ chatbot significantly improves the efficiency of information services and library management. Recommendations for future research include optimizing chatbot algorithms and enhancing application compatibility with various devices.